ANALISIS PENGUJIAN PERUBAHAN DAN PERBAIKAN TEGANGAN PADA PEMBEBANAN GENERATOR SINKRON DI LAB. KONVERSI ENERGI POLITEKNIK NEGERI MANADO - Lumondo, Nopri Aristo Samuel; Mandagi, Aldi Carlis; Loegimin, Maruto Swatara; Bijang, Nathaniel (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
A synchronous generator is a machine that converts mechanical energy into electrical energy, where the rotor speed is synchronized with the frequency of the generated voltage. Therefore, its existence plays a crucial role in maintaining service continuity.This study was conducted in the Energy Conversion Laboratory of Politeknik Negeri Manado, using a synchronous generator as the main object of investigation. One of the factors affecting its characteristics is the variation in generator load. In this research, an analysis was carried out on the voltage changes in a synchronous generator under varying load conditions, as well as efforts to improve voltage in order to maintain its stability.The research method involved experimental voltage measurements. The results of this study provide an understanding of the voltage characteristics of a synchronous generator when subjected to load variations, as well as voltage improvement achieved by increasing the rotational speed of the motor.